Catalyst for cracking waste polystyrene as well as preparation method and application of catalyst

By combining the FCC waste catalyst and metal oxide, a catalyst with large pore size and pore volume was prepared, which solved the problems of low catalyst activity and high cost, improved the yield of styrene and liquid product, and simplified the yield of styrene The process flow is completed.

CN119114046AActive Publication Date: 2024-12-13PETROCHINA CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202310659865.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-06
Publication Date
2024-12-13
Estimated Expiration
2043-06-06

AI Technical Summary

Technical Problem

The catalyst used for the cracking of waste polystyrene in the prior art has high cost and low activity, which affects the yield and process complexity of styrene.

Method used

The ground FCC waste catalyst is mixed with sodium pyrophosphate, water and ammonium carbonate, and then dried with calcium chloride solution to form microspheres, and roasted at high temperature to prepare a catalyst with large pore size and pore volume, metal oxide Disperse on the surface of the pore to improve activity.

Benefits of technology

The efficient activity and selectivity of the catalyst are achieved, the production cost is reduced, the process flow is simplified, and the yield of styrene and liquid product is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114046A_ABST
    Figure CN119114046A_ABST
Patent Text Reader

Abstract

The invention provides a catalyst for waste polystyrene cracking and a preparation method and application thereof, and the preparation method comprises the following steps: step 1, grinding an FCC waste catalyst, then mixing with sodium pyrophosphate and water, and then mixing with ammonium carbonate; 2, mixing the mixture obtained in the step 1 with a calcium chloride solution, and drying to prepare microspheres; and step 3, roasting the microspheres to obtain the catalyst for waste polystyrene cracking. The catalyst contains the FCC waste catalyst and the metal oxide, the catalyst has large pore diameter and pore volume due to the original pore structure and CO2 punching effect of the FCC waste catalyst, and the metal oxide is dispersed on the surface of the pore channel of the catalyst, so that the activity accessibility of the catalyst is improved, and the effective activity and selectivity of the catalyst are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a catalyst for cracking waste polystyrene and a preparation method and application thereof. The catalyst of the invention is mainly used for cracking waste polystyrene. Background Art

[0002] The use cycle of polymer chemicals is short. For example, when polystyrene is used as packaging material, its use cycle is short, so the discard rate is very high. Since polymers themselves are difficult to degrade, they are easy to cause environmental pollution.

[0003] CN1105351A discloses a method for producing light oil and gas by cracking, desulfurizing and reducing viscosity of inferior heavy oil waste plastics, using zinc oxide, ferric oxide and rare earth metal oxide as catalysts, and using an anchor stirrer and a liftable discharge device in the reactor to catalytically crack waste polystyrene, with a styrene yield of 35-60%. However, due to the small pore size of conventional metal oxides, larger polystyrene molecules are not easy to enter their inner surface, and most of them react on the outer surface, which not only affects their effective activity, but also reduces the selectivity of liquid products and styrene monomers. Therefore, the effective activity of the metal oxide catalyst in the invention is low, and the cracking styrene yield is less than 60%.

[0004] CN1220662A discloses that calcium oxide is used as a catalyst, mixed with waste polystyrene, heated to 150-250°C in a preheater, and then enters a cracking reactor for cracking at 350-500°C and a pressure of 0.005-0.02Mpa, and the styrene recovery rate reaches 70-85%. In this invention, waste polystyrene and catalyst need to be preheated and cracked under a certain pressure, which is complex in process and has a high production cost.

[0005] CN101891581A uses a mesoporous molecular sieve Mx / MCM-41 loaded with alkali metals / alkaline earth metals as a catalyst, performs a cracking reaction at 300-450°C under normal pressure or reduced pressure or nitrogen gas, and the liquid product yield is more than 95%, and the styrene content in the liquid product is more than 80%. The synthesis of the mesoporous molecular sieve Mx / MCM-41 catalyst of the invention requires an organic template, and the process is complicated and the cost is high.

[0006] CN1106371A uses specially modified Y-type molecular sieve and high-purity, high-specific-surface-area alumina to prepare waste polystyrene cracking catalyst, and the cracking reaction is carried out at 320-390°C, and the styrene yield is 62-65%. The synthesis of the medium-pore molecular sieve Mx / MCM-41 catalyst of the invention also requires an organic template, and the process is complicated and the cost is high.

[0007] Therefore, there is still a need in the art to study catalysts for cracking of waste polyethylene in order to reduce catalyst costs and improve catalyst activity. Summary of the invention

[0008] The main purpose of the present invention is to provide a catalyst for cracking waste polystyrene and a preparation method and application thereof, so as to overcome the defects of the catalyst for cracking waste polystyrene in the prior art, such as high cost and low activity.

[0009] In order to achieve the above object, the present invention provides a method for preparing a catalyst for cracking waste polystyrene, comprising the following steps:

[0010] Step 1, grinding the FCC spent catalyst, then mixing it with sodium pyrophosphate, water, and then mixing it with ammonium carbonate;

[0011] Step 2, mixing the mixture obtained in step 1 with a calcium chloride solution, and drying to prepare microspheres;

[0012] Step 3, calcining the microspheres to obtain a catalyst for cracking waste polystyrene.

[0013] The method for preparing a catalyst for cracking waste polystyrene of the present invention, wherein the particle size of the FCC waste catalyst after grinding is less than 10 μm.

[0014] The method for preparing a catalyst for cracking waste polystyrene of the present invention comprises the following steps: the mass ratio of the sodium pyrophosphate to the FCC waste catalyst is 0.01:1 to 0.1:1 based on the dry mass of the FCC waste catalyst; and the mass ratio of the water to the FCC waste catalyst is 2:1 to 3:1.

[0015] The method for preparing a catalyst for cracking waste polystyrene of the present invention comprises the following steps: the mass ratio of the FCC waste catalyst to the ammonium carbonate is 0.17:1 to 0.26:1, calculated on a dry basis.

[0016] The method for preparing a catalyst for cracking waste polystyrene of the present invention comprises the following steps: the calcium chloride solution is calculated based on the mass of calcium chloride, the FCC waste catalyst is calculated based on the mass of dry basis, and the mass ratio of the calcium chloride solution to the FCC waste catalyst is 0.1:1 to 0.3:1.

[0017] The method for preparing a catalyst for cracking waste polystyrene of the present invention comprises the following steps: mixing the FCC waste catalyst with sodium pyrophosphate and deionized water, and stirring the mixture for 1 to 2 hours.

[0018] The method for preparing a catalyst for cracking waste polystyrene according to the present invention comprises the following steps: the mixture obtained in step 1 is mixed with a calcium chloride solution and then stirred for 1 to 2 hours.

[0019] The method for preparing a catalyst for cracking waste polystyrene of the present invention comprises the following steps: the drying method in step 2 is spray drying; the microspheres in step 3 are calcined at a temperature of 830-900° C. for a calcination time of 1-3 hours.

[0020] In order to achieve the above object, the present invention also provides a catalyst for cracking waste polystyrene obtained by the above preparation method.

[0021] The catalyst of the present invention is used in the cracking of waste plastics, wherein the cracking conditions are: the cracking temperature is 330-380°C, the pressure is normal pressure, and the mass ratio of the catalyst to the waste polystyrene is 2wt%-15wt%.

[0022] Beneficial effects of the present invention:

[0023] The catalyst of the present invention contains FCC waste catalyst and metal oxide. The original pore structure of the FCC waste catalyst and the punching effect of CO2 make the catalyst have a larger pore diameter and pore volume, and the metal oxide is dispersed on the surface of the catalyst pore channel, which improves the active accessibility of the catalyst and improves the effective activity and selectivity of the catalyst.

[0024] The catalyst of the present invention adopts FCC waste catalyst, which not only solves the problem of treating FCC waste catalyst, but also realizes the reuse of FCC waste catalyst, and the process is simple and easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the pore size distribution diagram of the waste polystyrene cracking catalyst in Example 1. DETAILED DESCRIPTION

[0026] The technical scheme of the present invention is described in detail below. The following implementation modes are implemented on the premise of the technical scheme of the present invention, and a detailed implementation process is given. However, the protection scope of the present invention is not limited to the following implementation modes. The structures or experimental methods of specific conditions are not specified in the following implementation modes, and generally conventional conditions are followed.

[0027] The present invention provides a method for preparing a catalyst for cracking waste polystyrene, comprising the following steps:

[0028] Step 1, grinding the FCC spent catalyst, then mixing it with sodium pyrophosphate, water, and then mixing it with ammonium carbonate;

[0029] Step 2, mixing the mixture obtained in step 1 with a calcium chloride solution, and drying to prepare microspheres;

[0030] Step 3, calcining the microspheres to obtain a catalyst for cracking waste polystyrene.

[0031] At present, most of the FCC waste catalysts are generally disposed of by landfill. The regeneration processes of a few FCC waste catalysts mainly include acid washing, carbonylation-chlorination, sulfidation-oxidation and magnetic rotation to remove heavy metals and restore the activity of FCC waste catalysts. However, these methods have problems such as complicated processes and high regeneration costs.

[0032] The present invention prepares a catalyst with a specific structure by combining FCC waste catalyst and metal oxide. The original pore structure of the FCC waste catalyst and the punching effect of CO2 make it have a larger pore diameter and pore volume, and the metal oxide is dispersed on the surface of the pore channel. Therefore, the catalyst prepared by the present invention has good dispersibility for polyethylene macromolecules and good active accessibility, thereby making the catalyst have high catalytic activity and selectivity.

[0033] The present invention does not specifically limit the FCC waste catalyst, and any catalytic cracking catalyst discarded from the catalytic cracking process may be used. The present invention also does not specifically limit the structure and element content of the FCC waste catalyst.

[0034] In one embodiment, the present invention uses a ball mill to grind the FCC waste catalyst; in another embodiment, after the FCC waste catalyst is ground, its particle size is less than 10 μm.

[0035] In one embodiment, the FCC waste catalyst of the present invention is mixed with sodium pyrophosphate and water, and the weight ratio of sodium pyrophosphate to the FCC waste catalyst on a dry basis is 0.01:1-0.1:1, preferably 0.02:1-0.05:1; the mass ratio of water to the FCC waste catalyst is 2:1-3:1. After the FCC waste catalyst of the present invention is mixed with sodium pyrophosphate and water, it is stirred for, for example, 1-2 hours, and then mixed with ammonium carbonate. In another embodiment, the weight ratio of ammonium carbonate to the FCC waste catalyst on a dry basis is 0.17:1-0.26:1.

[0036] Step 2 is to mix the mixture obtained in step 1 with a calcium chloride solution, and dry the mixture to prepare microspheres.

[0037] The present invention does not particularly limit the concentration of the calcium chloride solution. In one embodiment, the mass content of calcium chloride in the calcium chloride solution is, for example, 35% by weight. The mass of the calcium chloride solution is calculated as calcium chloride, the mass of the FCC waste catalyst is calculated as the dry basis of the FCC waste catalyst, and the weight ratio of the calcium chloride solution to the FCC waste catalyst is 0.1:1-0.3:1, preferably 0.2:1-0.3:1.

[0038] In one embodiment, the mixture obtained in step 1 is mixed with the calcium chloride solution and then stirred for, for example, 1-2 hours. In another embodiment, the drying method is spray drying to prepare microspheres.

[0039] The microspheres are calcined to obtain a catalyst for cracking waste polystyrene. In one embodiment, the microspheres are calcined at 830-900° C. for 1-3 hours.

[0040] In summary, in the preparation of the catalyst of the present invention, sodium pyrophosphate plays a dispersing role, so that the calcium carbonate generated by the reaction of ammonium carbonate and calcium chloride is evenly dispersed. During high-temperature roasting, calcium carbonate generates calcium oxide and carbon dioxide. The punching effect of the generated carbon dioxide makes the catalyst have a larger pore size and pore volume. At the same time, calcium oxide as an active component is dispersed on the surface of the pores, which is beneficial to improving the effective activity of the catalyst.

[0041] The catalyst prepared by the method of the present invention has a large pore size and pore volume, and the metal oxide is dispersed on the surface of the pores. The catalyst of the present invention can be used to catalyze the cracking of waste polystyrene plastics, and the cracking conditions are, for example, a cracking temperature of 330 to 380° C., a pressure of normal pressure, and a mass ratio of the catalyst to the waste polystyrene of 2wt% to 15wt%. The present invention does not specifically limit the waste polystyrene plastics, such as various discarded instrument housings, lampshades, optical chemical instrument parts, transparent films, capacitor dielectric layers, etc.

[0042] The catalyst of the invention has good diffusion performance and can improve effective activity in cracking reaction, thereby improving liquid yield and styrene yield.

[0043] The technical solution of the present invention will be further described in detail below through specific examples. The waste polystyrene in the following examples and comparative examples is discarded instrument housings, lampshades, optical chemical instrument parts, transparent films, capacitor dielectric layers, etc. The polystyrene used in the examples and comparative examples is the same.

[0044] Source of raw materials or equipment: FCC waste catalyst (specific surface area of ​​113.7m 2 / g, pore volume is 0.127cm 3 / g), sodium pyrophosphate and ammonium carbonate were of analytical grade and produced by Sinopharm Group; calcium chloride solution (35w%) was produced by Shandong Rongfeng Chemical Co., Ltd.

[0045] Evaluation and analysis methods: The surface area and pore volume of the catalyst were determined by low-temperature nitrogen adsorption-desorption method, and the chlorine content of the oil was determined by gas chromatography (for the analysis method, see "Petrochemical Analysis Method (RIPP Experimental Method)", edited by Yang Cuiding et al., Science Press, published in 1990), and the catalyst reaction performance was evaluated using a small fixed fluidized bed.

[0046] Example 1

[0047] 303 g of ground FCC waste catalyst (dry basis) was mixed with 9.1 g of sodium pyrophosphate and 636 g of deionized water. After stirring for 1.2 hours, 63.6 g of ammonium carbonate was added and mixed evenly. The above slurry was then mixed with 181.8 g of calcium chloride solution and stirred for 2 hours. The mixture was spray-dried to form microspheres. The sprayed microspheres were calcined at 865°C for 1.1 hours to obtain waste polystyrene cracking catalyst C-1.

[0048] Using waste polystyrene as raw material, at a temperature of 355°C and a catalyst C-1:waste polystyrene ratio of 9 wt%, the liquid yield was 96.7%, of which the styrene yield was 85.3%.

[0049] Figure 1 is the pore size distribution diagram of the waste polystyrene cracking catalyst of Example 1, Figure 1 As shown, the catalyst prepared in Example 1 of the present invention has a good mesoporous structure and a double pore distribution. The two mesoporous distribution peaks are 3.8 nm and 11.7 nm, respectively, which can effectively promote the diffusion and mass transfer of polystyrene macromolecular raw materials and products.

[0050] Example 2

[0051] 356 g of ground FCC waste catalyst (dry basis) was mixed with 14.2 g of sodium pyrophosphate and 1060 g of deionized water. After stirring for 1.9 hours, 89 g of ammonium carbonate was added and mixed evenly. The above slurry was then mixed with 86.4 g of calcium chloride solution and stirred for 1.1 hours. The mixture was spray-dried to form microspheres. The spray microspheres were calcined at 890°C for 1.5 hours to obtain waste polystyrene cracking catalyst C-2.

[0052] Using waste polystyrene as raw material, at a temperature of 330°C and a catalyst C-3:waste polystyrene ratio of 5 wt%, the liquid yield was 95.3%, of which the styrene yield was 86.6%.

[0053] Example 3

[0054] 432 g of ground FCC waste catalyst (dry basis) was mixed with 8.7 g of sodium pyrophosphate and 1080 g of deionized water. After stirring for 1.5 hours, 73.5 g of ammonium carbonate was added and mixed evenly. The above slurry was then mixed with 101.8 g of calcium chloride solution. After stirring for 1.5 hours, it was spray-dried to form microspheres. The spray microspheres were calcined at 847°C for 2.9 hours to obtain waste polystyrene cracking catalyst C-3.

[0055] Using waste polystyrene as raw material, at a temperature of 375°C and a catalyst C-3:waste polystyrene ratio of 3 wt%, the liquid yield was 95.6%, of which the styrene yield was 85.7%.

[0056] Example 4

[0057] 369 g of ground FCC waste catalyst (dry basis) was mixed with 18.4 g of sodium pyrophosphate and 922 g of deionized water. After stirring for 1.7 hours, 95.9 g of ammonium carbonate was added and mixed evenly. The above slurry was then mixed with 110 g of calcium chloride solution and stirred for 1.1 hours. The mixture was spray-dried to form microspheres. The spray microspheres were calcined at 835°C for 2 hours to obtain waste polystyrene cracking catalyst C-4.

[0058] Using waste polystyrene as raw material, at a temperature of 335°C and a catalyst C-4:waste polystyrene ratio of 14 wt%, the liquid yield was 96.7%, of which the styrene yield was 86.1%.

[0059] Example 5

[0060] 373 g of ground FCC waste catalyst (dry basis) was mixed with 9.3 g of sodium pyrophosphate and 821 g of deionized water. After stirring for 1.1 hours, 84.8 g of ammonium carbonate was added and mixed evenly. The above slurry was then mixed with 242 g of calcium chloride solution and stirred for 1.5 hours. The mixture was spray-dried to form microspheres. The sprayed microspheres were calcined at 880°C for 1.3 hours to obtain waste polystyrene cracking catalyst C-5.

[0061] Using waste polystyrene as raw material, at a temperature of 360°C and a catalyst C-5:waste polystyrene ratio of 8 wt%, the liquid yield was 96.1%, of which the styrene yield was 85.7%.

[0062] Example 6

[0063] 406 g of ground FCC waste catalyst (dry basis) was mixed with 14.2 g of sodium pyrophosphate and 1096 g of deionized water. After stirring for 1.3 hours, 77.1 g of ammonium carbonate was added and mixed evenly. The above slurry was then mixed with 220 g of calcium chloride solution and stirred for 1.7 hours. The mixture was spray dried to form microspheres. The sprayed microspheres were calcined at 850°C for 2.5 hours to obtain waste polystyrene cracking catalyst C-6.

[0064] Using waste polystyrene as raw material, at a temperature of 380°C and a catalyst C-6:waste polystyrene ratio of 2 wt%, the liquid yield was 95.7%, of which the styrene yield was 85.1%.

[0065] Example 7

[0066] 467 g of ground FCC waste catalyst (dry basis) was mixed with 21 g of sodium pyrophosphate and 1120 g of deionized water. After stirring for 1.7 hours, 93.4 g of ammonium carbonate was added and mixed evenly. The above slurry was then mixed with 266 g of calcium chloride solution and stirred for 1.1 hours. The mixture was spray-dried to form microspheres. The spray microspheres were calcined at 830°C for 3 hours to obtain waste polystyrene cracking catalyst C-7.

[0067] Using waste polystyrene as raw material, at a temperature of 340°C and a catalyst C-6:waste polystyrene ratio of 6 wt%, the liquid yield was 96.8%, of which the styrene yield was 86.9%.

[0068] Comparative Example 1

[0069] 9.1 g of sodium pyrophosphate and 636 g of deionized water were mixed, stirred for 1.2 hours, and then 63.6 g of ammonium carbonate was added and mixed evenly. The above slurry was then mixed with 181.8 g of calcium chloride solution, stirred for 2 hours, and then spray-dried to form microspheres. The sprayed microspheres were calcined at 865°C for 1.1 hours to obtain waste polystyrene cracking catalyst D-1.

[0070] Using waste polystyrene as raw material, at a temperature of 355°C and a catalyst D-1:waste polystyrene ratio of 9 wt%, the liquid yield was 86.7%, of which the styrene yield was 82.4%.

[0071] Comparative Example 2

[0072] The waste FCC catalyst was calcined at 865°C for 1.1 hours to obtain the waste polystyrene cracking catalyst D-2.

[0073] Using waste polystyrene as raw material, at a temperature of 355°C and a catalyst D-2:waste polystyrene ratio of 9 wt%, the liquid yield was 79.8%, of which the styrene yield was 77.1%.

[0074] Comparative Example 3

[0075] Using waste polystyrene as raw material, under the reaction conditions of temperature 355°C and calcium oxide:waste polystyrene ratio of 9wt%, the liquid yield was 85.3%, of which the styrene yield was 77.2%.

[0076] It can be seen from the evaluation results of the catalysts in the above examples and comparative examples that the catalyst prepared by the method of the present invention is used in the waste polystyrene cracking process and has the characteristics of good catalyst activity accessibility, high liquid yield and high styrene yield.

[0077] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a catalyst for cracking waste polystyrene, characterized in that: The steps include: Step 1, grinding the FCC spent catalyst, then mixing it with sodium pyrophosphate, water, and then mixing it with ammonium carbonate; Step 2, mixing the mixture obtained in step 1 with a calcium chloride solution, and drying to prepare microspheres; Step 3, calcining the microspheres to obtain a catalyst for cracking waste polystyrene.

2. The method for preparing a catalyst for cracking waste polystyrene according to claim 1, characterized in that: The particle size of the FCC waste catalyst after grinding is less than 10 μm.

3. The method for preparing a catalyst for cracking waste polystyrene according to claim 1, characterized in that: The FCC waste catalyst is calculated on a dry basis, the mass ratio of the sodium pyrophosphate to the FCC waste catalyst is 0.01:1 to 0.1:1, and the mass ratio of the water to the FCC waste catalyst is 2:1 to 3:

1.

4. The method for preparing a catalyst for cracking waste polystyrene according to claim 1, characterized in that: The FCC waste catalyst is calculated on a dry basis, and the mass ratio of the ammonium carbonate to the FCC waste catalyst is 0.17:1 to 0.26:

1.

5. The method for preparing a catalyst for cracking waste polystyrene according to claim 1, characterized in that: The calcium chloride solution is calculated based on the mass of calcium chloride, and the FCC waste catalyst is calculated based on the mass of dry basis. The mass ratio of the calcium chloride solution to the FCC waste catalyst is 0.1:1 to 0.3:

1.

6. The method for preparing a catalyst for cracking waste polystyrene according to claim 1, characterized in that: The FCC waste catalyst is mixed with sodium pyrophosphate and deionized water and stirred for 1-2 hours.

7. The method for preparing a catalyst for cracking waste polystyrene according to claim 1, characterized in that: The mixture obtained in step 1 is mixed with the calcium chloride solution and stirred for 1-2 hours.

8. The method for preparing a catalyst for cracking waste polystyrene according to claim 1, characterized in that: The drying method in step 2 is spray drying; the temperature of the microspheres in step 3 is 830-900° C., and the calcination time is 1-3 hours.

9. A catalyst for cracking waste polystyrene obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the catalyst according to claim 9 in the cracking of waste plastics, characterized in that: The cracking conditions are as follows: the cracking temperature is 330-380° C., the pressure is normal pressure, and the mass ratio of the catalyst to the waste polystyrene is 2wt%-15wt%.

Citation Information

Patent Citations

  • Method for catalytically cracking waste plastics and apparatus for catalytically cracking waste plastics

    CN101374930A

  • Method for quickly preparing humic acid by polymerizing biomass material

    CN106317419A

  • Reactivation method for FCC waste catalyst

    CN107252692A

  • Method for preparation of methyl ethyl carbonate with co-precipitation catalyst

    CN107501095A

  • Mesoporous nano-microsphere nickel-magnesium-calcium composite oxide catalyst and application thereof

    CN114558624A